DETERMINATION OF PURCHASE DECISIONS AND CUSTOMER SATISFACTION: ANALYSIS OF BRAND IMAGE AND SERVICE QUALITY (REVIEW LITERATURE OF MARKETING MANAGEMENT) - Ali, Hapzi; Rivai Zainal, Veithzal; Rafqi Ilhamalimy, Ridho (Dinasti International Journal of Digital Business Management, 2021)
The purpose of writing Literature Review Papers is to determine the effect of service quality and brand image variables on purchasing decisions and customer satisfaction. With qualitative methods and Library Research. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results show that service quality affects purchasing decisions, service quality affects consumer satisfaction, brand image affects purchasing decisions, brand image affects consumer satisfaction and purchasing decisions affects consumer satisfaction.